2017
DOI: 10.21276/apalm.1357
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet indices in differentiating hypoproductive and hyperdestructive thrombocytopenia

Abstract: Background: During evaluation of thrombocytopenic patients, it is essential to identify the etiology, whether it is due to hypoproduction or hyperdestruction which will have impact on the management. Aim of study is to evaluate the variation and relationship of platelet indices in hypoproductive and hyperdestructive thrombocytopenia patients. Methods:A cross sectional study for a period of 2 months on Patients with thrombocytopenia. Platelet count, Plateletcrit (PCT), Platelet Distribution Width (PDW) and Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 12 publications
17
21
0
Order By: Relevance
“…In the present study group A included infections, neonatal TCPs, cardiac cases, pregnancy induced TCPs, renal, liver, sepsis, burns and immune thrombocytopenias (ITP) accounting to 75.3% of which infections were the majority number of cases similar to other studies. 8,13 In contrast, studies done by Numbenjapon T et al 15 and Khaleel KJ et al 16 found ITP being the majority of cases in group A. In the present study highest MPV and PDW values in group A category were seen in ITP cases similar to the other studies.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In the present study group A included infections, neonatal TCPs, cardiac cases, pregnancy induced TCPs, renal, liver, sepsis, burns and immune thrombocytopenias (ITP) accounting to 75.3% of which infections were the majority number of cases similar to other studies. 8,13 In contrast, studies done by Numbenjapon T et al 15 and Khaleel KJ et al 16 found ITP being the majority of cases in group A. In the present study highest MPV and PDW values in group A category were seen in ITP cases similar to the other studies.…”
Section: Discussionsupporting
confidence: 64%
“…Ages of the patients ranged from 1 day (neonatal cases) to 85 years similar to other studies. 8,[13][14][15][16][17][18][19][20] Patients were categorized into three groups according to the predominant mechanism of TCPs. Majority of the cases in the present study were of group A (75.4%), followed by group B (24%) and group C (0.6%) similar to the study done by Reddy 5)…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies conducted by Parveen and Vimal [14] and Gulati et al, [10] dengue fever comprised only 30.85% and 25.3% of cases, respectively. Malaria cases were higher in other studies when compared to our study [10,14,15] (Table 10). This difference may be attributed to the demographic variations and endemicity of the infection (Figure 1a and b).…”
Section: Discussionmentioning
confidence: 86%
“…The analyzers have the advantage of not only being quick but are also able to throw light on a wide variety of indices and minimize the inter-observer bias. [2,9,10] The analyzers also display a plateletogram along with numerical indices which are often overlooked. [4] Other than the routine platelet counts, which is the most commonly asked parameter, the other platelet indices like MPV [Mean platelet volume], PCT [plateletcrit] and PDW [platelet distribution width] are also available in the analyzer readings.…”
Section: Discussionmentioning
confidence: 99%
“…This approach will narrow differentials, avoid unnecessary investigations and aid in targeted management. [2] Manual methods for determination of hematological parameters in laboratories which are Manual methods for determination of hematological parameters in laboratories which are labor intensive and time consuming are now largely replaced by automated analyzers. These analyzers routinely give platelet histogram in addition to platelet count and indices at no extra cost.…”
Section: Introductionmentioning
confidence: 99%